Enzymatic deacidification of the rice bran oil and simultaneous preparation of phytosterol esters-enriched functional oil catalyzed by immobilized lipase arrays1. Issue 86 (18th September 2015) - Zheng, Mingming; Zhu, Jiuxia; Huang, Fenghong; Xiang, Xia; Shi, Jie; Deng, Qianchun; Ma, Fangli; Feng, Yuqi
<x xml:space="preserve">Abstract</x> Novel ordered mesoporous silica immobilized lipase arrays are described for enzymatic deacidification of the high-acid rice bran oil and simultaneous preparation of phytosterol esters-enriched functional oil.